English phonetics and pronunciation practice - Carley, Paul (Linguist); Mees, Inger M.; Collins, Beverley (Routledge, 2018)
"English Phonetics and Pronunciation Practice provides a unique introduction to basic articulatory phonetics for students of English. Built around an extensive collection of practice materials, this book teaches the pronunciation of modern standard non-regional British English to intermediate and advanced learners worldwide."--Provided by publisher.